Hairy Maggot of Chrysomya villeneuvi (Diptera: Calliphoridae), a Fly Species of Forensic Importance - Sukontason K. (2014)
We reported on the hairy maggot of Chrysomya villeneuvi Patton, collected from a human corpse in Thailand. Although the general morphology of the third instar closely resembled the more common hairy maggot blow fly, Chrysomya rufifacies (Macquart), the spines along the tubercles of each body segment could be used as a feature to distinguish between these species, with those of C. villeneuvi bearing sharp-ended spines that encircle the entire tubercle. Not only has the resemblance of a hairy appearance between C. villeneuvi and C. rufifacies larvae been documented but also their similarity in predacious feeding behavior. The differentiation between these two species is necessary for post-mortem interval estimation in the corpse.